Elevated Anandamide, Enhanced Recall of Fear Extinction, and Attenuated Stress Responses Following Inhibition of Fatty Acid Amide Hydrolase: A Randomized, Controlled Experimental Medicine Trial - Mayo, Leah M.; Asratian, Anna; Lindé, Johan; Morena, Maria; Haataja, Roosa; Hammar, Valter; Augier, Gaëlle; Hill, Matthew N.; Heilig, Markus (Biological psychiatry (1969), 2020)
Posttraumatic stress disorder, an area of large unmet medical needs, is characterized by persistence of fear memories and maladaptive stress responses. In rodents, elevation of the endocannabinoid anandamide due to inhibition of fatty acid amide hydrolase (FAAH) facilitates fear extinction and protects against the anxiogenic effects of stress. We recently reported that elevated anandamide levels in people homozygous for a loss-of-function FAAH mutation are associated with a similar phenotype, suggesting a translational validity of the preclinical findings. In this double-blind, placebo-controlled experimental medicine study, healthy adults were randomized to an FAAH inhibitor (PF-04457845, 4 mg orally, once daily; n = 16) or placebo (n = 29) for 10 days. On days 9 and 10, participants completed a task battery assessing psychophysiological indices of fear learning, stress reactivity, and stress-induced affective responses. FAAH inhibition produced a 10-fold increase in baseline anandamide. This was associated with potentiated recall of fear extinction memory when tested 24 hours after extinction training. FAAH inhibition also attenuated autonomic stress reactivity, assessed via electrodermal activity, and protected against stress-induced negative affect, measured via facial electromyography. Our data provide preliminary human evidence that FAAH inhibition can improve the recall of fear extinction memories and attenuate the anxiogenic effects of stress, in a direct translation of rodent findings. The beneficial effects of FAAH inhibition on fear extinction, as well as stress- and affect-related behaviors, provide a strong rationale for developing this drug class as a treatment for posttraumatic stress disorder.